GOVERNANCE OF ENERGY INTENSITY IMPLEMENTATION: CASE STUDY OF PT ALAMTRI RESOURCE INDONESIA TBK - Suryaningsum, Sri; Andhika, Bambang Mahendra; Roffiatun, Nelly (Count : Journal of Accounting, Business and Management, 2025)
This study analyzes the governance of energy intensity implementation at PT Alamtri Resource Indonesia Tbk. (2019-2023) through a quantitative descriptive approach, namely calculating energy intensity and then conducting a comparative analysis of similar sectors. The results show significant fluctuations: energy intensity jumped 54% (2020) and 202% (2023) during production expansion without technological innovation, but dropped drastically by 61% (2021) and 60% (2022) post-infrastructure investment. Comparatively, the company's performance is consistently above the average of the Indonesian mining sector (0.28 SBM/million Rp), with a gap of 20 times the minimum sector value (2019). This dynamic is influenced by internal factors (economic activity, technical efficiency) and external factors such as regulatory pressures on  Rencana Umum Energi Nasional (RUEN), dependence on national infrastructure (network losses of 8.2%), and fluctuations in commodity prices. The managerial implications emphasize continued investment in equipment updates, technology integration during expansion, and collaboration with governments to mitigate systemic challenges. These findings are the basis for operational policies to achieve national targets while mitigating the risk of inefficiency.